Self-determination in citizen science: diagnosing the applicability and implications for mutually beneficial settings - Waters, Paul (Kansas State University, 2018)
Citizen science is a method of carrying out scientific research with the help of untrained citizens. Citizen science carries multiple potential benefits for scientific inquiry, but in order to be effective must facilitate mutually beneficial settings. The most prevalent use of citizen science has been in ornithology. Bird based citizen science projects have been highly successful and have facilitated mutually beneficial projects. The field of citizen science is changing with the onset of new technologies. These technologies may expand the opportunities of citizen science, but it is important that a mutual benefit is maintained. This study uses self-determination theory, a theory of human psychological needs and motivations, to address motivational factors of bird based citizen science participation to provide a framework by which to maintain the necessary mutual benefit. This study consists of responses from an online survey administered to subscribers of birding listservs across the country. Analysis of the responses found that the need for relatedness is most consistently related to participants’ motivations. The suggestion is made that future citizen science efforts focus on the community building aspects of participation. Other nuances of the data and ideas for further research are discussed.
Keywords: Birding; Self-determination theoryCitizen science